Adaptive Features of Natural Killer Cells in Multiple Sclerosis - Moreira, Antía; Alari-Pahissa, Elisenda; Munteis, Elvira; Vera, Andrea; Zabalza, Ana; Llop, Mireia; Villarrubia, Noelia; Costa-García, Marcel; Álvarez-Lafuente, Roberto; Villar, Luisa María; López-Botet, Miguel; Martínez-Rodríguez, Jose E. (Frontiers in Immunology, 2019)
Human cytomegalovirus (HCMV) has been recently related with a lower susceptibility to multiple sclerosis (MS). HCMV promotes an adaptive development of NK cells bearing the CD94/NKG2C receptor with a characteristic phenotypic and functional profile. NK cells are proposed to play an immunoregulatory role in MS, and expansion of the NKG2C(+) subset was recently associated with reduced disability progression. To further explore this issue, additional adaptive NK cell markers, i.e. downregulation of FcεRIγ chain (FcRγ) and PLZF transcription factor, as well as antibody-dependent NK cell activation were assessed in controls and MS patients considering HCMV serology and clinical features. In line with previous reports, increased proportions of NKG2C(+), FcRγ(-) and PLZF(-) CD56dim NK cells were found in HCMV(+) cases. However, PLZF(-) NK cells were detected uncoupled from other adaptive markers within the CD56bright subset from HCMV(+) cases, and among CD56dim NK cells from HCMV(-) MS patients suggesting an additional effect of HCMV-independent factors in PLZF downregulation. Interferon-β therapy was associated with lower proportions of FcRγ(-) CD56dim NK cells in HCMV(+) and increased PLZF(-) CD56bright NK cells in HCMV(-) patients, pointing out to an influence of the cytokine on the expression of adaptive NK cell-associated markers. In addition, proportions of NKG2C(+) and FcRγ(-) NK cells differed in progressive MS patients as compared to controls and other clinical forms. Remarkably, an adaptive NK cell phenotype did not directly correlate with enhanced antibody-triggered degranulation and TNFα production in MS in contrast to controls. Altogether our results provide novel insights on the putative influence of HCMV and adaptive NK cells in MS.